Stalking on Campus: A Gendered Perspective on Target Congruence and Opportunity - Elvey, Kathryn (Criminal justice and behavior, 2018)
This study examines target congruence and lifestyle-routine activity behaviors as explanations of stalking victimization among college students, while also considering gender as a moderator in these relationships. Analysis of a nationwide sample of more than 75,000 students from 129 universities across the United States suggests that indicators of target antagonism, target gratifiability, and target vulnerability significantly predict stalking victimization. Indicators of lifestyle-routine activities—in particular, proximity to motivated offenders, exposure to motivated offenders, and target attractiveness—are also significantly related to stalking victimization. In addition, the importance of specific risk factors vary by gender. The results highlight the importance of target congruence as an expansion of lifestyle-routine activities theory, which can help to direct policies and prevention measures in a meaningful and systematic way.